Social Determinants of Disparities in Mortality Outcomes in Congenital Heart Disease: A Systematic Review and Meta-Analysis - Tran, Richard; Forman, Rebecca; Mossialos, Elias; Nasir, Khurram; Kulkarni, Aparna (Frontiers in Cardiovascular Medicine, 2022)
Background: Social determinants of health (SDoH) affect congenital heart disease (CHD) mortality across all forms and age groups. We sought to evaluate risk of mortality from specific SDoH stratified across CHD to guide interventions to alleviate this risk. Methods: We searched electronic databases between January 1980 and June 2019 and included studies that evaluated occurrence of CHD deaths and SDoH in English articles. Meta-analysis was performed if SDoH data were available in >= 3 studies. We included race/ethnicity, deprivation, insurance status, maternal age, maternal education, single/multiple pregnancy, hospital volume and geographic location of patients as SDoH. Data were pooled using random-effects model and outcome was reported as odds ratio (OR) with 95% confidence interval (CI). Results: Of 17,716 citations reviewed, 65 met inclusion criteria. Sixty-three were observational retrospective studies and two prospective. Of 546,981 patients, 34,080 died. Black patients with non-critical CHD in the first year of life (Odds Ratio 1.62 [95% confidence interval 1.47–1.79], I2 = 7.1%), with critical CHD as neonates (OR 1.27 [CI 1.08-1.55], I2= 0%) and in the first year (OR 1.68, [1.46-1.96], I2=0.3%) had increased mortality. Deprived patients, multiple pregnancies, patients born to mothers <18 years and with education <12 years, and patients on public insurance with critical CHD have greater likelihood of death after the neonatal period. Conclusion: This systematic review and meta-analysis found that Black patients with CHD are particularly vulnerable for mortality. Numerous SDoH that affect mortality were identified for specific time points in CHD course that may guide interventions, future research and policy.